Blue eyes blue - Clapton, Eric; Cavallo, Rob; Reprise Records (United States : Reprise Records, 1999)
Contains the single taken from the album Eric Clapton Greatest Hits Album.
Edit version.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English